2006
DOI: 10.1111/j.1600-6143.2006.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Allograft Function on a Tacrolimus-Based, Pred-Free Maintenance Immunosuppression Comparing Sirolimus vs. MMF

Abstract: It is not known how different steroid-free immuno-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 30 publications
5
60
0
Order By: Relevance
“…Fifty-four trials 51,[72][73][74][76][77][78][79][81][82][83][84][85][87][88][89][91][92][93]95,96,[98][99][100][102][103][104][105][106][108][109][110][111][112][113][115][116][117][118][119][120]124,127,131,134,135,139,141,[143][144][145][153][154][155] did not report any information on allocation concealment, whereas 20 trials 71,…”
Section: Concealment Of Allocationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-four trials 51,[72][73][74][76][77][78][79][81][82][83][84][85][87][88][89][91][92][93]95,96,[98][99][100][102][103][104][105][106][108][109][110][111][112][113][115][116][117][118][119][120]124,127,131,134,135,139,141,[143][144][145][153][154][155] did not report any information on allocation concealment, whereas 20 trials 71,…”
Section: Concealment Of Allocationmentioning
confidence: 99%
“…Fifty-seven trials (48 maintenance studies, 51,58,77,[80][81][82]84,86,94,99,100,102,[104][105][106][107][108][109][113][114][115][116][117][119][120][121][124][125][126][127]131,132,134,138,139,[141][142][143][144][145][146][147]149,150,152,154,156,157 eight induction studies 71,72,74,87,97,128,137 and one study …”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[14][15][16][17][18][19][20][21][22] In several studies, reduced renal function was observed when SRL was combined with standard doses of CNI, including the two Phase 3 randomized, controlled trials comparing SRL with placebo and azathioprine (AZA), respectively, in combination with full-dose CsA and steroids. 14,15 Despite lower acute rejection rates, SRL-treated patients were found to have lower glomerular fi ltration rates (GFRs) through the fi rst year post transplant.…”
Section: Mtor-is In De Novo Renal Transplantationmentioning
confidence: 99%
“…14,15 Despite lower acute rejection rates, SRL-treated patients were found to have lower glomerular fi ltration rates (GFRs) through the fi rst year post transplant. Similarly, when SRL was combined with full-dose TAC, renal function was worse in SRL-treated patients compared with either mycophenolate mofetil (MMF) 16 or reduced TAC, 19 which resulted in termination of the standard TAC arm in the latter study. These fi ndings were confi rmed in two pivotal trials with EVR, further supporting the rationale to lower CNI dosages when combined with mTOR-Is.…”
Section: Mtor-is In De Novo Renal Transplantationmentioning
confidence: 99%